Developing sustainable service user involvement practices in mental health services in Sweden: the “Userinvolve” research program protocol - Markström, Urban; Näslund, Hilda; Schön, Ulla-Karin; Rosenberg, David; Bejerholm, Ulrika; Gustavsson, Anneli; Jansson, Mårten; Argentzell, Elisabeth; Grim, Katarina; Engdahl, Patrik; Nouf, Faten; Lilliehorn, Sara; et al. (Frontiers in Psychiatry, 2023)
Background The purpose of this paper is to outline the protocol for the research program “UserInvolve,” with the aim of developing sustainable, service user involvement practices in mental health services in Sweden. Methods This protocol outlines the knowledge gap and aim of the UserInvolve-program. It further provides an overview of the research infrastructure, with specific focus on the organization and management of the program as well as the design of the six underlying research projects. These six research projects form the core of the UserInvolve-program and will be carried out during a six-year period (2022–2027). The projects are focused on examining articulations of experiential knowledge in user collectives, on four specific user involvement interventions (shared decision-making, peer support, user-focused monitoring, and systemic involvement methods) and on developing theory and method on co-production in mental health research and practice. Results or conclusion The knowledge gained through the co-production approach will be disseminated throughout the program years, targeting service users, welfare actors and the research community. Based on these research activities, our impact goals relate to strengthening the legitimacy of and methods for co-production in the mental health research and practice field.